Bendable, Free-Standing Calcite Thin Films - Nakamura, Shiho; Naka, Kensuke (Langmuir, 2015)
Since the hardness and toughness of natural nacre are determined by hierarchical microstructures with organic matters, it is of great importance to control the microstructures of artificial free-standing CaCO3 thin films. However, the fabrication of such films has so far been quite limited, to the extent that their mechanical properties have not been reported. To address this, free-standing calcite thin films were prepared through repeated cycles of layer-by-layer deposition of vaterite precursor composite particles with organic polymers, followed by a phase transition to calcite. In this way, two distinct calcite thin film types were produced based on either 3.2 or 1.0 wt % organic material, with subsequent three-point bending tests revealing that both exhibit elastic bending prior to fracture. More importantly, by increasing the organic content from 1.0 to 3.2 wt %, the bending strength increased from 0.95 ± 0.26 MPa to 1.90 ± 0.21 MPa.